Are Smart Cities Smart Managers for Digital Equity? Focusing on spatial autocorrelation among 229 cities in South Korea - Jung Ho Kim; Dayoung Lee; Junseok Hwang; Junmin Lee (International Telecommunications Society (ITS), 2024)
In the relentless pursuit of urban prosperity and sustainability, cities worldwide are undergoing transformative changes, spurred by the Fourth Industrial Revolution and digital transformation(DX). At the forefront of this evolution are Smart Cities, which leverage cutting-edge information and communication technologies (ICT) to enhance public services and improve the overall quality of life for their inhabitants. These technologically advanced cities utilize data-driven decision-making to optimize various sectors, from mobility to governance, promising a new era of urban living. However, technologies that enable smart cities to develop, also risk deepening the digital divide. ICT infrastructure is a crucial element to smart cities' development, but it often overlooks the disparities in digital access and skills among different demographic groups. Preliminary research predominantly focuses on the technological and industrial components necessary for developing smart cities but falls short in addressing the social dimension, particularly the digital divide. This study aims to bridge this gap by exploring the digital divide within the context of Korean smart cities. The research conducts an empirical analysis of whole South Korean 229 cities and analyzes the impact of ICT infrastructure provision, knowledge-intensive industry specialization, and local governance capability alleviating or exacerbating digital divide.
Keywords: 330; Smart City; Digital Divide; ICT Infrastructure; Knowledge-Intensive Indusrtry; Governance Capability; Spatial Autocorrelation